Starting Modes of Asynchronous Electric Drives Taking into Account the Resistance of the Line of the Power Supply System - Krasnoshapka, N. D.; Pushkar, M. V. (Visnyk of Vinnytsia Politechnical Institute, 2022)
The issues of the influence of the active resistance of the power supply line on the starting characteristics of asynchronous electric drives are considered. In long-distance low-voltage distribution networks, the voltage at the end consumers may decrease due to a significant drop in the power line. This voltage drop will depend on the amount of current in the line. Starting unregulated induction motors with short-circuited rotor is characterized by a relatively small value of starting torque at high starting current values, which will increase the voltage drop in the transmission line during start-up and, consequently, reduce starting torque proportional to the square of applied voltage. Thus, the mode of operation of the electric drive with frequent starts will negatively affect the operation of other consumers of electricity. A comparison of starting characteristics using a serial asynchronous motor with a short-circuited rotor and modified with massive end ferromagnetic screens of rotor circuit elements outside the working air gap, which provides the formation of mechanical characteristics of the “excavator” type. The influence of the active resistance of the transmission line on the values of starting torques and currents for electric drives with both types of motors is investigated. It is established that the modified asynchronous motor due to the larger value of the starting torque allows to start the electric drive at static torque equal to the nominal torque of the motor at the studied change of line resistance to 1.5 relative to the active resistance of the motor stator winding, while in electric drive serial motor starting torque becomes less than the nominal with additional resistances greater than 0.8 relative to the active resistance of the stator winding. In turn, higher values of starting torque provide the electric drive with the modified asynchronous motor much less time of start and consumption of active energy, than at application of the serial car with identical conditions of start. Thus, the electric drive with an induction motor with massive end ferromagnetic screens of fragments of the rotor circuit outside the working air gap has significant advantages over the serial motor in the case of operation with frequent starts.